THE MAIN PROBLEMS OF TAX INCENTIVES FOR INVESTMENT IN THE INNOVATIVE DEVELOPMENT OF THE REAL SECTOR OF THE RUSSIAN ECONOMY - L. Kostina; Y. Popelysheva (Вестник университета)
Today, the main role in the process of increasing investment activity is assigned to state regulation. The pushing influence on the investment response of potential investors can be provided by various methods of regulation, among which are those that are implemented through tax incentives for investment in the innovative development of the real sector of the Russian economy. The authors of the article considers the main problems of tax stimulation of innovation activity in the real sector of the economy of the Russian Federation. In addition, forms and instruments of tax incentives for innovation have been studied.